IKLIM KESELAMATAN, KOMPETENSI DAN PERILAKU KESELAMATAN PADA PELAUT - Kurniawan, Dicha Anugraha; Widanti, Nurul Sih; Syanti, Wanda Rahma (Fakultas Psikologi Universitas Hang Tuah, 2023)
Abstract. This research aimed to determine the influence of safety climate and competence on safety behavior among seafarers at PT. Rajawali Berlian Surabaya. This research utilized a quantitative correlation approach. Respondents in this study were 60 sailors selected using saturated sampling techniques. The measuring instruments used include the safety climate scale, competency scale, and safety behavior scale. Data were analyzed using multiple regression techniques. The research results showed that safety climate and competence influenced safety behavior among sailors by 70.3%. Other results revealed that safety climate contributed to safety behavior among seafarers by 67.3%; competency in safety behavior among sailors was 51.6%. These research findings can be used as an intervention design related to work safety for seafarers.